Defoliation effects toward the oil palm, Elaeis Guineensis sex determination and differentiation (a review) / Nur Dianah Hafizah Ismail - Hafizah Ismail, Nur Dianah (Faculty of Plantation and Agrotechnology, 2016)
Oil palm is a monoecious species of the palm subfamily Arecoideae, which produces functionally unisexual male and female inflorescences in an alternating cycle of the same plant. Thus, the species is qualified as temporally dioecious. The sex ratio of an oil palm can be influenced by both genetic and environmental factors. Besides, physiological stress like severe defoliation has been known in some studies can induce a higher frequency of males and abortions but it is not known how such factors interact with endogenous cycles nor the developmental state when sex is determined known with accuracy. This is because the inflorescence sex determination and differentiation also has been identified that it is a complex process where phonological information can only be obtained from the plants growing in the field. In term of defoliation, data from previous studies has shown that defoliation will affected on the inflorescence production. This lead to a decreasing in sex ratio and increasing in abortion rate causing a reduction in the number of yield. So, for the yield predicting and forecasting purpose, the effects from oil palm defoliation on the sex differentiation and differentiation can give impacts on those purpose.